Frontispiece: Smart Nanodrug with Nuclear Localization Sequences in the Presence of MMP‐2 To Overcome Biobarriers and Drug Resistance. Issue 8 (6th February 2019) - Mo, Liuting; Zhao, Zilong; Hu, Xiaoxiao; Yu, Xuan; Peng, Yongbo; Liu, Hui; Xiong, Mengyi; Fu, Ting; Jiang, Ying; Zhang, Xiaobing; Tan, Weihong
Abstract : Nanoparticle‐based drug formulations have been impeded by a series of physiological barriers in achieving therapeutic outcomes, including opsonization and sequestration by the mononuclear phagocyte system, elevated interstitial fluid pressure and dense interstitial matrix, endo‐lysosomal trapping and drug efflux pumps. To address this issue, this work develops size‐controllable stealth doxorubicin‐loaded nanodrug coated with CD47 peptides based on supramolecular chemistry. The frontispiece graphic shows the smart nanodrug efficiently decrease macrophage sequestration, disassemble into smaller drugs in the tumor microenvironment, enters into tumor cell nucleus and overcoming drug resistance. For more information see the Communication by X. Zhang, W. Tan et al. on page 1895 .